Production of photoionized plasmas in the laboratory using X-ray line radiation - White,S; Irwin,R; Warwick,R; Gribakin,G; Sarri,G; Keenan,FP; Riley,D; Rose,SJ; Hill,E; Ferland,GJ; Han,B; Wang,F; et al. (Physical Review E, 2018)
In this paper we report the experimental implementation of a theoretically proposed technique for creating a photoionized plasma in the laboratory using x-ray line radiation. Using a Sn laser plasma to irradiate an Ar gas target, the photoionization parameter, ξ=4πF/Ne, reached values of order 50ergcms−1, where F is the radiation flux in ergcm−2s−1. The significance of this is that this technique allows us to mimic effective spectral radiation temperatures in excess of 1 keV. We show that our plasma starts to be collisionally dominated before the peak of the x-ray drive. However, the technique is extendable to higher-energy laser systems to create plasmas with parameters relevant to benchmarking codes used to model astrophysical objects.